Origin of mantle peridotites from the Vourinos Ophiolite Complex, Greece, as deduced from Cr-spinel morphological and chemical variations - Kapsiotis,A.N. (Journal of Geosciences, 2013)
The Vourinos Ophiolite Complex in north-western Greece represents a fragment of oceanic lithosphere emplaced after the Late Jurassic closure of the Neotethyan Pindos Ocean. This Ophiolite Complex consists mainly of a well-preserved mantle sequence dominated by peridotite and chromitite. Based on petrographic features, four distinct peridotite varieties can be distinguished in the Vourinos mantle suite: i) normal harzburgite (Opx ≤ 15 vol. %), ii) transitional harzburgite (Opx < 15 vol. %), iii) coarse-grained dunite and iv) fine-grained dunite. Chromian spinel morphology, based on DR# (degree of roundness) measurements, varies systematically from harzburgitic to dunitic rocks. Anhedral chromian spinel occurs in normal harzburgite (DR# < 0.40), whereas in the other studied peridotite types this mineral is more euhedral (DR# > 0.40). The Cr# [Cr/(Cr + Al)] in chromian spinel increases from normal harzburgite to coarse-grained dunite, varying between 0.47 and 0.84. Such a variation in chromian spinel composition indicates a multi-stage melting evolution for the Vourinos mantle suite. Chromian spinel from fine-grained dunite bears similarities in terms of Cr# and Mg# [Mg/(Mg + Fe2+)] with chromian spinel from the neighboring chromitites, which implies a common origin for both lithologies. Chromian spinel morphological and compositional data indicate that after chromitite and fine-grained dunite formation a remnant boninite melt could have invaded the adjacent peridotites, modifying their accessory chromian spinels or even crystallizing new chromian spinel grains. Further evidence for that episode of melt percolation is provided by a few harzburgitic rock samples, which may be locally enriched in LREE exhibiting U-shaped chondrite-normalized REE patterns. Such patterns are characteristic of interaction between the depleted mantle peridotite and hydrous boninitic melt. The studied peridotites are interpreted as refractory residues whose initial composition was locally modified by mantle metasomatism in the fore-arc region in a supra-subduction zone.
Keywords: chromian spinel; partial melting; mantle metasomatism; peridotites; ophiolites